Research methods in taxation history - Frecknall-Hughes, Jane (Now Publishers, 2016)
This paper is an attempt to consider the research methods used in taxation history, which is an area that has attracted increased academic interest in recent years. The paper looks at the various routes that may provide an entry into studying taxation generally and at the inherently interdisciplinary/multidisciplinary nature of the subject. If taxation is researched through different disciplinary lenses, the focus of research changes, which brings to the forefront questions about the most appropriate research methods to use – questions which become more complex when taxation history is considered, along with fact that the different disciplines have their own histories which may themselves impact on taxation history research. The paper looks in detail at social science research methods, also legal research (as ‘different’ from other social science disciplines to which taxation is linked), as well as history and legal history, to evaluate research methods used in those areas. It shows that tax history can be researched in several ways from different perspectives, which show an underlying rigour and more similarity than is at first apparent.